Compressive Strength of Compacted Clay-Sand Mixes. (6th November 2014) - Khan, Faseel Suleman; Azam, Shahid; Raghunandan, Mavinakere Eshwaraiah; Clark, Ryan
Abstract : The use of sand to improve the strength of natural clays provides a viable alternative for civil infrastructure construction involving earthwork. The main objective of this note was to investigate the compressive strength of compacted clay-sand mixes. A natural clay of high plasticity was mixed with 20% and 40% sand (SP) and their compaction and strength properties were determined. Results indicated that the investigated materials exhibited a brittle behaviour on the dry side of optimum and a ductile behaviour on the wet side of optimum. For each material, the compressive strength increased with an increase in density following a power law function. Conversely, the compressive strength increased with decreasing water content of the material following a similar function. Finally, the compressive strength decreased with an increase in sand content because of increased material heterogeneity and loss of sand grains from the sides during shearing.